PERANAN GEOMORFOLOGI TERHADAP PEMBANGUNAN TPA (TEMPAT PEMBUANGAN AKHIR) DAERAH CIPATAT, KABUPATEN BANDUNG BARAT - Murni Sulastri; Muhammad Agil Prasetyo; Pradnya Paramarta Raditya Rendra; Nana Sulaksana; Muhammad Tobibi Pratama Pohan (PPSDM Geominerba, 2020)
The research area is in the Sarimukti region, Cipatat District, West Bandung Regency, West Java Province. Geographically is at 107 ° 19’51.9024 “EL—107 ° 22’34.9392” EL and - 6 ° 49’56.7156 “SL —-6 ° 47’14.8344” SL. The research area is hill which is dominated by volcanic rock. Based on the physiographic aspects, the research area is include in Bandung Zone. Geological mapping aims to determine the geomorphological conditions in the construction of landfill site in the research area using field and studio approaches. Some of the methods used include geomorphological aspects as well as an assessment of the regional stage of the landfill weighting criteria. The results in the research area are the geomorphological unit of volcanic hills gentle slopes, the geomorphological unit of volcanic hills slightly steep slopes, the geomorphological unit of volcanic hills steep slope, and the geomorphological unit of denudational hills slightly slopes. According to the geomorphological and weighting analysis of the regional stage, it is assessed that this land needs to be subjected to a rather heavy technology engineering, or it is moved to land that is deemed more suitable for landfill.